Polyphenol Release from Wheat Bran Using Ethanol-Based Organosolv Treatment and Acid/Alkaline Catalysis: Process Modeling Based on Severity and Response Surface Optimization - Eirini S. Papadaki; Dimitrios Palaiogiannis; Stavros I. Lalas; Paraskevi Mitlianga; Dimitris P. Makris (MDPI AG, 2022)
Wheat bran (WB) is globally a major food industry waste, with a high prospect as a bioresource in the production of precious polyphenolic phytochemicals. In this framework, the current investigation had as objectives (i) to use ethanol organosolv treatment and study the effect of acid and alkali catalysts on releasing bound polyphenols, (ii) establish linear and quadratic models of polyphenol recovery based on severity and response surface, and (iii) examine the polyphenolic composition of the extracts generated. Using sulfuric acid and sodium hydroxide as the acid and the alkali catalyst, respectively, it was found that the correlation of combined severity factor with total polyphenol yield was significant in the acid catalysis, but a highly significant correlation in the alkali-catalyzed process was established with modified severity factor, which takes into consideration catalyst concentration, instead of pH. Optimization of the process with response surface confirmed that polyphenol release from WB was linked to treatment time, but also catalyst concentration. Under optimized conditions, the acid- and alkali-catalyzed processes afforded total polyphenol yields of 10.93 ± 0.62 and 19.76 ± 0.76 mg ferulic acid equivalents g−1 dry mass, respectively. Examination of the polyphenolic composition revealed that the alkali-catalyzed process had a striking effect on releasing ferulic acid, but the acid catalysis was insufficient in this regard. The outcome concerning the antioxidant properties was contradictory with respect to the antiradical activity and ferric-reducing power of the extracts, a fact most probably attributed to extract constituents other than ferulic acid. The process modeling proposed herein may be valuable in assessing both process effectiveness and severity, with a perspective of establishing WB treatments that would provide maximum polyphenol recovery with minimum harshness and cost.